ACTFL Analysis of Arabic Writing Proficiency in a Textbook - Tsany Gorna Mara Putra Zulkarnaen; Hikmah Maulani (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the proficiency level characteristics of al-mahārah al-kitābah (writing skills) in the 12th-grade Madrasah Aliyah Arabic textbook based on the American Council on the Teaching of Foreign Languages (ACTFL) Writing Proficiency Guidelines 2024. A qualitative content analysis approach was applied, utilizing the writing tasks in the textbook and the ACTFL guidelines as the primary data sources. Data collection was carried out through documentation and systematic close reading techniques, which were then analyzed using the FACT instrument covering the aspects of Functions, Accuracy, Context/Content, and Text Type. The results indicate that the writing tasks in the textbook are distributed across the proficiency range from Novice High to Intermediate Low. Two types of tasks are categorized at the Novice High level as they require learners to recombine learned vocabulary and structures to form simple sentences on familiar topics. Meanwhile, one task type is categorized at the Intermediate Low level because it requires the production of original, connected sentences based on familiar thematic content. These findings indicate that the textbook is partially aligned with ACTFL standards, although progression toward higher proficiency levels remains limited.